2004
DOI: 10.1007/s00240-004-0424-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anti-estrogens on the androgen receptor activity and cell proliferation in prostate cancer cells

Abstract: Although some anti-estrogens have been reported to inhibit the proliferation of prostate cancer cells, few studies on the mechanism by which they suppress the growth of prostate cancer have been reported. We investigated, for the first time, whether anti-estrogens modulate the transactivation activity of the androgen receptor (AR) in prostate cancer cells. In DU-145 cells transfected with AR, the transactivation activity of AR was inhibited by tamoxifen and toremifene, even in the presence of 10 nM of DHT. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…LNCaP cells were treated with carnosol, flutamide, tamoxifen, carnosol/flutamide, carnosol/tamoxifen, or tamoxifen/flutamide for 24 h. In agreement with other investigators (7, 2123), we observed an increase in AR and ER-α activity with treatment of flutamide or tamoxifen individually as shown by Western blot analysis in Figure 5C. However, upon co-treatment of flutamide or tamoxifen with carnosol, a decrease in protein expression of AR and ER- α was observed.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…LNCaP cells were treated with carnosol, flutamide, tamoxifen, carnosol/flutamide, carnosol/tamoxifen, or tamoxifen/flutamide for 24 h. In agreement with other investigators (7, 2123), we observed an increase in AR and ER-α activity with treatment of flutamide or tamoxifen individually as shown by Western blot analysis in Figure 5C. However, upon co-treatment of flutamide or tamoxifen with carnosol, a decrease in protein expression of AR and ER- α was observed.…”
Section: Resultssupporting
confidence: 60%
“…Toremifene has a bimodal effect where it functioned as an antagonist at lower concentrations, however, as the dose was increased, it functioned as an agonist in LNCaP cells (7). Limitations of fulvestrant as a dual AR and ER modulator include 1) the AR antagonist effect is saturable regardless of increasing the dose, 2) it can not bind to the mutated AR (T877) that is found in LNCaP cells, and 3) it did not exhibit any effect in a Phase II clinical trial in castration resistant PCa (8, 9).…”
Section: Introductionmentioning
confidence: 99%
“…Contradictory to this, in a previous study using European eels which show similar reproductive strategy to the species studied here, authors suggested ER-mediation of androgen action based on the inhibition of androgen action by tamoxifen [12]. Recently, however, tamoxifen has been proved to be not only anti-estrogenic, but also antiandrogenic in some occasions [20]. Furthermore, MT has been shown to have 10,000-100,000 times less affinity for ER than E 2 in a fish [17].…”
Section: Discussionmentioning
confidence: 73%
“…5). Recent studies by Kawashima et al (57) showed that ICI decreased DHT stimulation of the androgen-responsive mouse mammary tumor virus-luciferase reporter in LNCaP cells. ER ligands, including ICI, have been shown to inhibit DHT stimulation of PSA transcriptional activity in PC-3 and DU145 cells cotransfected with AR and ER-a and ER-h expression plasmids (58).…”
Section: Discussionmentioning
confidence: 99%